Brothers in arms? How the IRA and EOKA insurgencies transcended the local and became transnational. (4th July 2021) - Edwards, Aaron; Hadjiathanasiou, Maria
ABSTRACT: Throughout the 1950s Britain faced unprecedented challenges to its imperial rule. Civil disobedience, insurgency and terrorism gripped its colonies as the flames of nationalism and anti-colonialism burned brightly across the world. In two of Britain's most important Cold War strategic outposts, Northern Ireland and Cyprus, insurgents belonging to the IRA and EOKA launched armed campaigns to undermine British rule. This article examines the insurgencies on both islands in the period 1955–59, comparing the respective approaches taken by the IRA and EOKA to guerrilla warfare. Drawing on original English and Greek language sources, as well as other empirical evidence, the article argues that the IRA and EOKA interpreted their struggles in complementary ways as part of a broader national liberation struggle, which, above all, suggests a shared understanding of British imperialism. Admittedly, beyond a mutually perceived 'brotherly bond', IRA leaders did not apply specific military lessons they had learned from members of EOKA while in English prisons in the 1950s until the much later Northern Ireland 'Troubles'. Nevertheless, we argue that it is important to look at the genealogy of ideas for it reveals broader patterns regarding the organisational learning of militant groups engaged in campaigns against a common enemy.